Viruses in weeds in Dioscorea yam fields in Nigeria - Asala, S.; Alegbejo, M.D.; Kashina, B.D.; Banwo, O.O.; Shinngu, C.P. (2014)
The presence of viruses in yam leaves and the presence of weeds in close proximity to yam fields have been shown to be associated with diminished tuber yield. But the precise role of weeds as alternative hosts of viruses infecting yam has not been systematically studied. Therefore, leaf samples of weeds were collected from Dioscorea yam fields in FCT-Abuja, and five States of the Guinea Savanna agro-ecological zone of Nigeria in 2009 and 2010, and analysed by Enzyme-Linked Immuno-absorbance Assay (ELISA) and Polymerase Chain Reaction for viruses. Fifty-four and 70% of samples collected during the two years, respectively, were infected with Yam mosaic virus, Cucumber mosaic virus, Cowpea mild mottle virus, Pepper venial mosaic virus, Telfeiria mosaic virus, Cowpea yellow mosaic virus and Badnavirus (DaBV). The weeds and viruses were Hibiscus esculentus Moench (YMV, CMV and CPMMV), Amaranthus spinosus Linn (CMV, YMV), Physalis angulata L (YMV, CMV), Procumbane Linn (CMV), Phyllanthus amarus Shum (YMV, CMV, CPMMV), Ludwigia abyssinica A. Rich (YMV), Galinsoga culiata L. (YMV), Eclipta prostrate Linn (YMV), Justicia flara Vahl (YMV, CMV), Euphorbia heterophylla Linn (YMV, CMV), Melanpodium divaricatum L. (YMV, CMV) and Saccivlepsis Africana Hubb (YMV), Melanpodium divaricatum L. (CPMMV), Crotalaria rutusa L. (YMV, CMV), Aspelia bussei O. Hoffin (CPMMV), Aneilema acquinotide P. Beauv (CPMMV), Pueraria phaseloides Linn (YMV), Platostoma Africana P. (YMV), Conyza summtrensis Retz (YMV, BCMV, PVMV, TeMV), Chroniolea oduratiu L. R (YMV, CYMV), Mitracarpus villosus D.C(CMV) and Sclerocarpus africanus Jacq (BCMV, PVMV, TeMV, Badnavirus). Weeds surrounding yam plants may serve as alternative hosts of viruses.The presence of viruses in yam leaves and the presence of weeds in close proximity to yam fields have been shown to be associated with diminished tuber yield. But the precise role of weeds as alternative hosts of viruses infecting yam has not been systematically studied. Therefore, leaf samples of weeds were collected from Dioscorea yam fields in FCT-Abuja, and five States of the Guinea Savanna agro-ecological zone of Nigeria in 2009 and 2010, and analysed by Enzyme-Linked Immuno-absorbance Assay (ELISA) and Polymerase Chain Reaction for viruses. Fifty-four and 70% of samples collected during the two years, respectively, were infected with Yam mosaic virus, Cucumber mosaic virus, Cowpea mild mottle virus, Pepper venial mosaic virus, Telfeiria mosaic virus, Cowpea yellow mosaic virus and Badnavirus (DaBV). The weeds and viruses were Hibiscus esculentus Moench (YMV, CMV and CPMMV), Amaranthus spinosus Linn (CMV, YMV), Physalis angulata L (YMV, CMV), Procumbane Linn (CMV), Phyllanthus amarus Shum (YMV, CMV, CPMMV), Ludwigia abyssinica A. Rich (YMV), Galinsoga culiata L. (YMV), Eclipta prostrate Linn (YMV), Justicia flara Vahl (YMV, CMV), Euphorbia heterophylla Linn (YMV, CMV), Melanpodium divaricatum L. (YMV, CMV) and Saccivlepsis Africana Hubb (YMV), Melanpodium divaricatum L. (CPMMV), Crotalaria rutusa L. (YMV, CMV), Aspelia bussei O. Hoffin (CPMMV), Aneilema acquinotide P. Beauv (CPMMV), Pueraria phaseloides Linn (YMV), Platostoma Africana P. (YMV), Conyza summtrensis Retz (YMV, BCMV, PVMV, TeMV), Chroniolea oduratiu L. R (YMV, CYMV), Mitracarpus villosus D.C(CMV) and Sclerocarpus africanus Jacq (BCMV, PVMV, TeMV, Badnavirus). Weeds surrounding yam plants may serve as alternative hosts of viruses.The presence of viruses in yam leaves and the presence of weeds in close proximity to yam fields have been shown to be associated with diminished tuber yield. But the precise role of weeds as alternative hosts of viruses infecting yam has not been systematically studied. Therefore, leaf samples of weeds were collected from Dioscorea yam fields in FCT-Abuja, and five States of the Guinea Savanna agro-ecological zone of Nigeria in 2009 and 2010, and analysed by Enzyme-Linked Immuno-absorbance Assay (ELISA) and Polymerase Chain Reaction for viruses. Fifty-four and 70% of samples collected during the two years, respectively, were infected with Yam mosaic virus, Cucumber mosaic virus, Cowpea mild mottle virus, Pepper venial mosaic virus, Telfeiria mosaic virus, Cowpea yellow mosaic virus and Badnavirus (DaBV). The weeds and viruses were Hibiscus esculentus Moench (YMV, CMV and CPMMV), Amaranthus spinosus Linn (CMV, YMV), Physalis angulata L (YMV, CMV), Procumbane Linn (CMV), Phyllanthus amarus Shum (YMV, CMV, CPMMV), Ludwigia abyssinica A. Rich (YMV), Galinsoga culiata L. (YMV), Eclipta prostrate Linn (YMV), Justicia flara Vahl (YMV, CMV), Euphorbia heterophylla Linn (YMV, CMV), Melanpodium divaricatum L. (YMV, CMV) and Saccivlepsis Africana Hubb (YMV), Melanpodium divaricatum L. (CPMMV), Crotalaria rutusa L. (YMV, CMV), Aspelia bussei O. Hoffin (CPMMV), Aneilema acquinotide P. Beauv (CPMMV), Pueraria phaseloides Linn (YMV), Platostoma Africana P. (YMV), Conyza summtrensis Retz (YMV, BCMV, PVMV, TeMV), Chroniolea oduratiu L. R (YMV, CYMV), Mitracarpus villosus D.C(CMV) and Sclerocarpus africanus Jacq (BCMV, PVMV, TeMV, Badnavirus). Weeds surrounding yam plants may serve as alternative hosts of viruses.The presence of viruses in yam leaves and the presence of weeds in close proximity to yam fields have been shown to be associated with diminished tuber yield. But the precise role of weeds as alternative hosts of viruses infecting yam has not been systematically studied. Therefore, leaf samples of weeds were collected from Dioscorea yam fields in FCT-Abuja, and five States of the Guinea Savanna agro-ecological zone of Nigeria in 2009 and 2010, and analysed by Enzyme-Linked Immuno-absorbance Assay (ELISA) and Polymerase Chain Reaction for viruses. Fifty-four and 70% of samples collected during the two years, respectively, were infected with Yam mosaic virus, Cucumber mosaic virus, Cowpea mild mottle virus, Pepper venial mosaic virus, Telfeiria mosaic virus, Cowpea yellow mosaic virus and Badnavirus (DaBV). The weeds and viruses were Hibiscus esculentus Moench (YMV, CMV and CPMMV), Amaranthus spinosus Linn (CMV, YMV), Physalis angulata L (YMV, CMV), Procumbane Linn (CMV), Phyllanthus amarus Shum (YMV, CMV, CPMMV), Ludwigia abyssinica A. Rich (YMV), Galinsoga culiata L. (YMV), Eclipta prostrate Linn (YMV), Justicia flara Vahl (YMV, CMV), Euphorbia heterophylla Linn (YMV, CMV), Melanpodium divaricatum L. (YMV, CMV) and Saccivlepsis Africana Hubb (YMV), Melanpodium divaricatum L. (CPMMV), Crotalaria rutusa L. (YMV, CMV), Aspelia bussei O. Hoffin (CPMMV), Aneilema acquinotide P. Beauv (CPMMV), Pueraria phaseloides Linn (YMV), Platostoma Africana P. (YMV), Conyza summtrensis Retz (YMV, BCMV, PVMV, TeMV), Chroniolea oduratiu L. R (YMV, CYMV), Mitracarpus villosus D.C(CMV) and Sclerocarpus africanus Jacq (BCMV, PVMV, TeMV, Badnavirus). Weeds surrounding yam plants may serve as alternative hosts of viruses.The presence of viruses in yam leaves and the presence of weeds in close proximity to yam fields have been shown to be associated with diminished tuber yield. But the precise role of weeds as alternative hosts of viruses infecting yam has not been systematically studied. Therefore, leaf samples of weeds were collected from Dioscorea yam fields in FCT-Abuja, and five States of the Guinea Savanna agro-ecological zone of Nigeria in 2009 and 2010, and analysed by Enzyme-Linked Immuno-absorbance Assay (ELISA) and Polymerase Chain Reaction for viruses. Fifty-four and 70% of samples collected during the two years, respectively, were infected with Yam mosaic virus, Cucumber mosaic virus, Cowpea mild mottle virus, Pepper venial mosaic virus, Telfeiria mosaic virus, Cowpea yellow mosaic virus and Badnavirus (DaBV). The weeds and viruses were Hibiscus esculentus Moench (YMV, CMV and CPMMV), Amaranthus spinosus Linn (CMV, YMV), Physalis angulata L (YMV, CMV), Procumbane Linn (CMV), Phyllanthus amarus Shum (YMV, CMV, CPMMV), Ludwigia abyssinica A. Rich (YMV), Galinsoga culiata L. (YMV), Eclipta prostrate Linn (YMV), Justicia flara Vahl (YMV, CMV), Euphorbia heterophylla Linn (YMV, CMV), Melanpodium divaricatum L. (YMV, CMV) and Saccivlepsis Africana Hubb (YMV), Melanpodium divaricatum L. (CPMMV), Crotalaria rutusa L. (YMV, CMV), Aspelia bussei O. Hoffin (CPMMV), Aneilema acquinotide P. Beauv (CPMMV), Pueraria phaseloides Linn (YMV), Platostoma Africana P. (YMV), Conyza summtrensis Retz (YMV, BCMV, PVMV, TeMV), Chroniolea oduratiu L. R (YMV, CYMV), Mitracarpus villosus D.C(CMV) and Sclerocarpus africanus Jacq (BCMV, PVMV, TeMV, Badnavirus). Weeds surrounding yam plants may serve as alternative hosts of viruses.The presence of viruses in yam leaves and the presence of weeds in close proximity to yam fields have been shown to be associated with diminished tuber yield. But the precise role of weeds as alternative hosts of viruses infecting yam has not been systematically studied. Therefore, leaf samples of weeds were collected from Dioscorea yam fields in FCT-Abuja, and five States of the Guinea Savanna agro-ecological zone of Nigeria in 2009 and 2010, and analysed by Enzyme-Linked Immuno-absorbance Assay (ELISA) and Polymerase Chain Reaction for viruses. Fifty-four and 70% of samples collected during the two years, respectively, were infected with Yam mosaic virus, Cucumber mosaic virus, Cowpea mild mottle virus, Pepper venial mosaic virus, Telfeiria mosaic virus, Cowpea yellow mosaic virus and Badnavirus (DaBV). The weeds and viruses were Hibiscus esculentus Moench (YMV, CMV and CPMMV), Amaranthus spinosus Linn (CMV, YMV), Physalis angulata L (YMV, CMV), Procumbane Linn (CMV), Phyllanthus amarus Shum (YMV, CMV, CPMMV), Ludwigia abyssinica A. Rich (YMV), Galinsoga culiata L. (YMV), Eclipta prostrate Linn (YMV), Justicia flara Vahl (YMV, CMV), Euphorbia heterophylla Linn (YMV, CMV), Melanpodium divaricatum L. (YMV, CMV) and Saccivlepsis Africana Hubb (YMV), Melanpodium divaricatum L. (CPMMV), Crotalaria rutusa L. (YMV, CMV), Aspelia bussei O. Hoffin (CPMMV), Aneilema acquinotide P. Beauv (CPMMV), Pueraria phaseloides Linn (YMV), Platostoma Africana P. (YMV), Conyza summtrensis Retz (YMV, BCMV, PVMV, TeMV), Chroniolea oduratiu L. R (YMV, CYMV), Mitracarpus villosus D.C(CMV) and Sclerocarpus africanus Jacq (BCMV, PVMV, TeMV, Badnavirus). Weeds surrounding yam plants may serve as alternative hosts of viruses.